Rhizosphere microbial and metabolic shifts under climate extremes during the early crop growth season in mediterranean environment - Luisa Maria Manici; Francesco Caputo; Flavio Fornasier; Bruno Morello; Claudia Di Bene; Simone Bregaglio (Rhizosphere, 2026)

The PhenoMeNals framework for grapevine yield and quality prediction - Simone Bregaglio; Sofia Bajocco (Agricultural and Forest Meteorology, 2026)

Phenological variability reveals environmental gradients in European beech forests - Carlotta Ferrara; Simone Bregaglio; Francesco Chianucci; Carlo Ricotta; Sofia Bajocco (International Journal of Biometeorology, 2026)

CrYP: An open-source Google earth engine tool for spatially explicit crop yield predictions - Lorenzo Crecco; Sofia Bajocco; Simone Bregaglio (Computers and Electronics in Agriculture, 2025)

Exploring the relationships between ground observations and remotely sensed hazelnut spring phenology - Sofia Bajocco; Mara Di Giulio; Abdoul Hamid Mohamed Sallah; Simone Bregaglio (International Journal of Biometeorology, 2025)
Crop phenology is very important in regular crop monitoring. Generally, phenology is monitored through field observation surveys or satellite data. The relationships between ground observations and remotely sensed derived phenological data can enable near-real-time monitoring over large areas, which has never been attempted on hazelnuts. In this study, we extracted phenological metrics derived from MODIS Enhanced Vegetation Index (EVI) in hazelnut production regions and compared them with the spring ground phenological data (BBCH scale) from orchards located in the same area of Turkey over the period from 2019 to 2022. We observed a specific temporal dynamic between remote sensing phenometrics and ground observations. The metrics Greenup, Upturning Date, and Threshold 20% metrics corresponded to the early of EVI growth and were synchronous with the female flowering of hazelnut and ending before bud break. The metrics Threshold 50% and Start of season were associated with the steepest portion of the EVI curve, i.e., canopy greening and thickening, and occurred between ovaries enlargement and leaves unfolding. The metrics Peak of Season, Stabilization Date, and Maturity corresponded to the end of spring vegetative growth. The main outcomes are that (i) female flowering occurred before 20% of vegetation development (BBCH 64P occurred about one month before Threshold 20%), (ii) phenometrics from satellite remote sensing (i.e., Upturning Date and Threshold 20%) well-reflected leaf emergence (r s = 0.30 and r s = 0.32, respectively; p < 0.05) and unfolding (r s = 0.35 and r s = 0.39, respectively; p < 0.05), and (iii) cluster appearance temporally aligned with the peak of the EVI curve (Stabilization Date and BBCH 71P differed by around 4 days). Our method is transferable to operational phenology monitoring, and future applications will consider the senescence season and the effect of environmental variability on the comprehension of vegetation dynamics.

A fuzzy logic evaluation of synergies and trade-offs between agricultural production and climate change mitigation - Roberta Calone; Angela Fiore; Guido Pellis; Maria Luz Cayuela; Gabriele Mongiano; Alessandra Lagomarsino; Simone Bregaglio (Journal of Cleaner Production, 2024)

Improving crop yield prediction accuracy by embedding phenological heterogeneity into model parameter sets - Simone Bregaglio; Fabrizio Ginaldi; Elisabetta Raparelli; Gianni Fila; Sofia Bajocco (Agricultural Systems, 2023)

A process-based model to simulate sugarcane orange rust severity from weather data in Southern Brazil - Taynara Tuany Borges Valeriano; Glauco de Souza Rolim; Luisa Maria Manici; Laura Giustarini; Simone Bregaglio (International Journal of Biometeorology, 2021)

Susceptibility of novel Italian rice varieties to panicle blast under field conditions - Gabriele Mongiano; Patrizia Titone; Simone Bregaglio; Luigi Tamborini (European Journal of Plant Pathology, 2021)

Uncertainties in predicting rice yield by current crop models under a wide range of climatic conditions - Tao Li; Toshihiro Hasegawa; Xinyou Yin; Yan Zhu; Kenneth Boote; Myriam Adam; Simone Bregaglio; Samuel Buis; Roberto Confalonieri; Tamon Fumoto; Donald Gaydon; Manuel Marcaida; et al. (Global Change Biology, 2015)
Predicting rice ( Oryza sativa ) productivity under future climates is important for global food security. Ecophysiological crop models in combination with climate model outputs are commonly used in yield prediction, but uncertainties associated with crop models remain largely unquantified. We evaluated 13 rice models against multi‐year experimental yield data at four sites with diverse climatic conditions in Asia and examined whether different modeling approaches on major physiological processes attribute to the uncertainties of prediction to field measured yields and to the uncertainties of sensitivity to changes in temperature and CO 2 concentration [ CO 2 ]. We also examined whether a use of an ensemble of crop models can reduce the uncertainties. Individual models did not consistently reproduce both experimental and regional yields well, and uncertainty was larger at the warmest and coolest sites. The variation in yield projections was larger among crop models than variation resulting from 16 global climate model‐based scenarios. However, the mean of predictions of all crop models reproduced experimental data, with an uncertainty of less than 10% of measured yields. Using an ensemble of eight models calibrated only for phenology or five models calibrated in detail resulted in the uncertainty equivalent to that of the measured yield in well‐controlled agronomic field experiments. Sensitivity analysis indicates the necessity to improve the accuracy in predicting both biomass and harvest index in response to increasing [ CO 2 ] and temperature.

An integrated evaluation of thirteen modelling solutions for the generation of hourly values of air relative humidity - Simone Bregaglio; Marcello Donatelli; Roberto Confalonieri; Marco Acutis; Simone Orlandini (Theoretical and Applied Climatology, 2010)